From Thyroid Uptake to Molecular Imaging – A Journey of Nuclear Medicine in Bangladesh - Khan, Mohafizul Hoque; Hasan, Mizanul (Bangladesh Journal of Nuclear Medicine, 2017)
Abstract not available Bangladesh J. Nuclear Med. 18(1): 8, January 2015